A comparison of islamic banking and profitability determinants in Malaysia and Indonesia / Suhaili Shohairi - Shohairi, Suhaili (Faculty of Business Management, 2017)
Malaysia and Indonesia are two countries that have implemented the concept of Islamic finance in their banking industries. Hence, Islamic banking and conventional banking are competing among themselves to satisfy customer and fulfil their customer expectation. As similar to Conventional bank, Islamic bank objective is to attain a greater profit of increasing owner’s wealth by achieving of high return on investment; particularly for the owner as well as the depositor. The banking sector profitability contribute in economies and makes economies to endure negative as well as financial shock that lead to the contribution in financial system stability. This leads to great challenges for the banks in order to maintain and increase their performance. Therefore, the aim of this study is to determine which factors that will significantly affect the Islamic bank profitability in Malaysia and Indonesia in order to enhance their performance. In order to achieve the study objective and to answer the question, Fixed Effect Modelshow the best method and results in order to determine the relationship of the variables towards the Islamic banking profitability. In this study, it found that for bank specific factor, Total Equity to Total Asset (TETA), Total Loan to Total Asset(TLTA)show a significant impact towards Islamic Banking profitability in Malaysia while Total Equity to Total Asset(TETA) and interest margin have significant impact for Indonesia Islamic banking profitability. On the other hand for macroeconomic factor only GDP show significant impact to Malaysia but in Indonesia macroeconomic factors did not give any significant impact towards their Islamic banking profitability.